Silicified coal adsorbents for adsorption of Cu(II) from the aqueous Solution: Non-Linear kinetic and isotherm studies. (2022) - Muslim, Abrar; Abubakar; Nurul Alam, Pocut; Usman, Husni; Randa, Gusti; Haris Widayat, Agus; Yahya Al Hakim, Andy; Hadibarata, Tony
Abstract: Silicified coal which can reduce the quantity and quality of coal production, is an uneconomic impure-coal. This study aims to develop adsorbents from silicified coal by washing and activating it using aquades and NaOH, respectively. FTIR spectroscopy revealed active sites of Si-O bending and Si-O stretching for adsorption of Cu(II) onto silicified coal adsorbents (SCA). The characterization of silicified coal using XRD, XRF and INAA FUS-ICP confirmed that the amorphous SCA consisted of 67.11–78.80 wt% of SiO2, 0.33–0.60 wt% of CaO, 0.30–0.40 wt% of Fe2 O3, and 20.09–32.25 wt% of LOI. SEM images confirmed different shape and size of pores on the adsorbents. The effect of contact time, initial Cu(II) concentration in the aqueous solution, and activator NaOH concentration on adsorption capacity were investigated by conducting batch mode experiments at room temperature, atmospheric pressure and pH 5. The non-linear pseudo-first order and pseudo-second order models were used for the adsorption kinetics, and the non-linear models of Langmuir, Freundlich, and BET were taken for the adsorption isotherm. Levenberg-Marquardt method was taken to minimize the sum of squared error (SSE) between the experimental and model results. The results showed that Cu(II) adsorption on the SCA fitted very well by non-linear pseudo-second order model (average SSE = 2.222 and R 2  = 0.9825 on average) with a maximum equilibrium adsorption capacity of 13.165 mg/g and adsorption rate of 0.025 g/mg.min. In addition, it was favorable adsorption by non-linear model of Langmuir (average SSE = 1.049 and R 2  = 0.995) with a maximum mono-layer adsorption capacity of 14.358 mg/g.